Legal Protection Bumi Putera Joint Life Insurance Policyholders - Khanifa Fauziah; Gunardi Lie; Moody Rizqy Syailendra (PT ARRUS Intelektual Indonesia, 2023)
This study aims to examine the legal protection provided to customers of life insurance policyholders in Bumi Putera, focusing on product transparency, fair and fast claim procedures, as well as appeal and lawsuit procedures. The method used field research with a qualitative approach through in-depth interviews with customers and related parties in Bumi Putera. The data collection techniques used were document studies and in-depth interviews. The collected data were analyzed by qualitative analysis methods, namely data reduction, data presentation, and conclusions. This research is expected to provide useful recommendations for Bumi Putera in improving legal protection for life insurance policyholder customers.